European financial coalition against commercial sexual exploitation of children online: report (Europol, 2015)
The aim of this report is to provide an update to the Strategic Assessment of Commercial Sexual Exploitation of Children Online published in October 2013 in the framework of European Financial Coalition (EFC). In addition to presenting the 2013 facts and figures, it also looks at other essential factors in this area. Technological expansion, growing Internet coverage and the widespread availability of mobile devices are increasingly digitalising our society. Criminals that sexually exploit children online are becoming more entrepreneurial with these technological developments and profiting financially. Europol’s European Cybercrime Centre (EC3) have produced a strategic assessment analysing the threats and trends of online child sexual exploitation (CSE), in order to recommend solutions and enable law enforcement and the private sector to jointly prevent and combat these horrific crimes.　The report has been drafted by EC3 for the European Financial Coalition against Commercial Sexual Abuse of Children Online (EFC), which brings together key actors from law enforcement, private industry and civil society in Europe to fight CSE.